Formulasi Kebijakan UMK dan Peran Advokasi Gubernur Jawa Timur dalam Penetapan Upah 2023–2024 - Amma Fathuurrahmaan; Andries Lionardo (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This research is motivated by the complexity of the formulation of the Regency/City Minimum Wage (UMK) policy in East Java Province, which is not only technocratic but also influenced by political dynamics and multi-actor interactions. The determination of the UMK as stipulated in East Java Governor Regulation Number 75 of 2022 and Number 78 of 2023 demonstrates the strategic role of the governor not only as a policymaker but also as a policy advocate in bridging the interests of workers and business actors. This study aims to analyze the UMK policy formulation process, the role of the governor, interaction patterns between actors, and factors influencing policy quality. The research method used is a descriptive qualitative approach with a literature study technique. Data were obtained from policy documents, academic literature, and relevant empirical media sources. Data analysis was carried out through data reduction, data presentation, and drawing conclusions using the theoretical framework of policy formulation, the Multiple Streams Framework (MSF), the Advocacy Coalition Framework (ACF), and a multi-actor governance approach. The research findings indicate that the formulation of MSE policy in East Java is the result of dynamic interactions between the government, labor unions, and business actors, involving negotiation and political compromise. The governor plays a crucial role as a policymaker and advocate in maintaining a balance of interests and the stability of industrial relations. Technocratic factors such as inflation and economic growth, as well as political factors such as interest group pressure, simultaneously influence policy decisions. However, transparency and accountability in the policy formulation process still need to be improved. This research recommends a participatory, transparent, and adaptive model for MSE policy formulation through strengthening tripartite dialogue, utilizing open data, and optimizing the roles of the governor and the Regional People's Representative Council (DPRD) in multi-actor policy governance.